Laser cladding method for improving wear resistance of cladding layer on surface of stainless steel substrate

Through the laser cladding method, a high-performance cladding layer is formed on the surface of the stainless steel matrix using wire or powder spare materials, which solves the problem of insufficient wear resistance of the surface cladding layer on the stainless steel matrix in the prior art, and achieves a comprehensive improvement of hardness, corrosion resistance and wear resistance.

CN119506868APending Publication Date: 2025-02-25XIAN UNVERSITY OF ARTS & SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411686536.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the wear resistance of the surface cladding layer of stainless steel substrate, resulting in insufficient surface performance of metal workpieces in high pressure, high temperature or easy wear environments and short service life.

Method used

The laser cladding method is adopted, and silk or powder spare material is used as the laser cladding material. By adjusting the process parameters and material ratio, a high-performance cladding layer is formed to enhance the hardness, corrosion resistance and wear resistance of the metal matrix.

Benefits of technology

The wear resistance, corrosion resistance and hardness of the surface cladding layer of stainless steel substrate has been significantly improved, the friction coefficient is reduced, and the service life of metal workpieces has been extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506868A_ABST
    Figure CN119506868A_ABST
Patent Text Reader

Abstract

The invention relates to a laser cladding method for improving wear resistance of a cladding layer on the surface of a stainless steel matrix, and belongs to the technical field of metal material surface engineering, the laser cladding method comprises the following steps: S1, selecting a metal matrix, and cleaning the metal matrix; s2, a laser cladding material is selected, the laser cladding material is pretreated, and a laser cladding standby material is obtained; s3, a laser cladding process is adopted, and the laser cladding standby material in the step S2 is cladded on the surface of the metal matrix prepared in the step S1; the metal matrix in the step S1 is a 27SiMn steel base material; the laser cladding material in the step S2 comprises any one of a wire standby material or a powder standby material. The prepared cladding layer can show better hardness, wear resistance and corrosion resistance, so that the comprehensive performance of a metal matrix is improved, and great economic benefits can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material surface engineering, in particular to a laser cladding method for improving the wear resistance of a cladding layer on the surface of a stainless steel substrate. Background Art

[0002] In industrial production, many metal workpieces work in high-pressure, high-temperature, corrosive or wear-prone environments. The failure forms of parts include fracture, deformation and surface loss, among which surface loss is the most common failure form. Improving the surface properties of metal workpieces is the key to extending the service life of metal workpieces.

[0003] At present, laser cladding, surfacing, spraying, electrodeposition and vapor deposition are all commonly used metal workpiece surface strengthening technologies. Laser cladding is an advanced metal surface strengthening technology and a widely used remanufacturing technology. It has the characteristics of small dilution rate, dense cladding layer, high metallurgical bonding, high material utilization rate and environmental protection. It melts and solidifies the metal workpiece and the cladding layer material in a laser beam to form a cladding layer with high metallurgical bonding performance.

[0004] The cladding layer materials of laser cladding mainly include metal materials, high entropy alloys, ceramic materials, composite materials, etc. Among them, metal materials mainly include self-fluxing alloys such as iron-based, nickel-based, and cobalt-based; ceramic materials are mainly divided into carbides, borides, and oxides. Ceramic materials are quite different from most alloy matrix materials of laser cladding, so the bonding performance is poor. They can be combined with metal-based materials to make composite materials to improve the properties of the cladding layer.

[0005] In view of the above-mentioned technical phenomena, the inventors believe that the selection of cladding layer materials is crucial to the success of laser cladding, which directly affects the performance and application areas of the cladding layer. Therefore, it is urgent to develop a material that can enhance the performance of metal workpieces so that it can be processed on the surface of metal workpieces through laser cladding process. Summary of the invention

[0006] The object of the present invention is to provide a laser cladding method for improving the wear resistance of a cladding layer on the surface of a stainless steel substrate, so as to enhance the comprehensive performance of the hardness, wear resistance and corrosion resistance of the metal substrate.

[0007] The present invention provides a laser cladding method for improving the wear resistance of a cladding layer on a stainless steel substrate surface, which adopts the following technical solution:

[0008] A laser cladding method for improving the wear resistance of a cladding layer on a surface of a stainless steel substrate comprises the following steps:

[0009] S1. Select a metal substrate and clean the metal substrate;

[0010] S2, selecting laser cladding materials, pre-treating the laser cladding materials, and obtaining laser cladding spare materials;

[0011] S3, using a laser cladding process to clad the laser cladding spare material in step S2 on the surface of the metal substrate prepared in step S1;

[0012] The metal substrate in step S1 is a 27SiMn steel substrate;

[0013] The laser cladding material in step S2 includes any one of wire material or powder material.

[0014] Preferably, the 27SiMn steel substrate comprises the following components in weight percentage: 0.24-0.32% C, 1.10-1.40% Si, 1.10-1.40% Mn, 0.10-0.30% Cr, 0.10-0.30% Ni, 0.10-0.30% Cu, 0.05-0.15% Mo and the balance Fe.

[0015] Preferably, the wire material spares in step S2 include 17-4PH wire material spares and 420 wire material spares;

[0016] The diameter of the spare wire material in step S2 is 1.2 mm.

[0017] Preferably, the mass ratio of the 17-4PH wire material reserve and the 420 wire material reserve in step S2 is (1-2): (1-3).

[0018] Preferably, when the laser cladding material in step S2 is selected from the spare wire material, the pretreatment of the laser cladding material in step S2 is to preheat the spare wire material to 800-850° C. in advance.

[0019] Preferably, when the laser cladding material in step S2 is selected as spare wire material, the laser cladding process in step S3 is to set the laser wavelength to 1064nm, the spot diameter to 4mm, the spare wire material tray is installed on the wire feeding wheel of the laser cladding equipment, and extended to the conductive nozzle, the feeding method is lateral wire feeding, nitrogen with a purity of 99.99% is selected as the protective gas, the power is adjusted to 2800W, the scanning speed is 25mm / s, and the total wire feeding speed is 62mm / s.

[0020] Preferably, the powder reserve material in step S2 includes 17-4PH powder reserve material;

[0021] The particle size of the 17-4PH powder stock is 45-100 μm.

[0022] Preferably, when the laser cladding material in step S2 is selected from powdered stock, the powdered stock in step S2 is placed in a planetary ball mill for ball milling, with the rotation speed set to 150 rpm and running for 2 hours.

[0023] Preferably, when the laser cladding material in step S2 is selected as powder stock, the laser cladding process in step S3 is to set the laser wavelength to 900-1080nm, the spot diameter to 3mm, and use the pre-set powder method to spread the powder stock on the metal substrate with a thickness of 1mm, select nitrogen as the protective gas, adjust the power to 1200-2000W, the scanning speed to 6-10mm / s, and the overlap rate to 40%.

[0024] Preferably, the powder material in step S2 further comprises one or more of TiC powder, B element, Mo element and C element;

[0025] The mass fraction of TiC powder in the powder material in step S2 is 0-1%, and the particle size of TiC is 45-109 μm;

[0026] The mass fraction of element B in the powder material in step S2 is 0-1.4%;

[0027] The mass fraction of Mo element in the powder material in step S2 is 0-0.15%;

[0028] The mass fraction of the C element in the powder material in step S2 is 0-1%.

[0029] In summary, the present invention includes the following beneficial technical effects:

[0030] 1. The present invention selects either wire material or powder material as laser cladding material, and uses a laser cladding process to enhance the hardness and corrosion resistance of the metal matrix and reduce the friction coefficient of the metal matrix, so that the metal matrix has good comprehensive performance.

[0031] 2. When the wire material is used as spare material, the process parameters of the laser cladding process are adjusted to ensure that the cladding layer has no defects such as pores and cracks on a macro scale, and the cladding layer forms a good combination with the substrate.

[0032] 3. When using spare wire materials, by adjusting the ratio between 17-4PH spare wire materials and 420 spare wire materials, the hardness of the cladding layer is as high as 626.6HV. 0.3 The lowest friction coefficient is 0.55, and the optimal wear volume is 0.035mm 3 , so that the cladding layer has better comprehensive performance.

[0033] 4. When powdered materials are used, the process parameters of the laser cladding process are adjusted to ensure that the cladding layer has no defects such as pores and cracks on a macro scale, and the cladding layer forms a good bond with the substrate.

[0034] 5. When powder materials are used as spare materials, the effects of the dosage of TiC, B, Mo and C on the cladding layer are studied. TiC powder can significantly improve the hardness and wear resistance of the cladding layer. The addition of Mo makes the structure finer and reduces the martensite spacing. C is beneficial to hardness and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a cross-sectional macroscopic morphology of the cladding layer prepared in Examples 1-4 of the present invention.

[0036] Figure 2 It is the XRD spectrum of the cladding layer prepared in Examples 1-4 of the present invention.

[0037] Figure 3 3 is a microhardness diagram of the cladding layer obtained by Examples 1-4 of the present invention.

[0038] Figure 4 Graph showing the coefficient of friction of the cladding layers obtained in Examples 1-4 of the present invention.

[0039] Figure 5 It is the wear morphology diagram of the cladding layer obtained by Examples 1-4 of the present invention.

[0040] Figure 6 1 is a polarization curve diagram of the cladding layer obtained by Examples 1-4 of the present invention.

[0041] Figure 7 Graph showing the hardness of the cladding layers obtained from Examples 5-11 of the present invention.

[0042] Figure 8 The cross-sectional macroscopic morphology of the cladding layer obtained by Examples 12-15 of the present invention is shown in FIG.

[0043] Fig. 9 It is the XRD spectrum of the cladding layer prepared by Examples 12-15 of the present invention.

[0044] Fig.10 It is a microstructure diagram of the cladding layer obtained by Examples 12-15 of the present invention.

[0045] Fig.11 It is a microhardness curve diagram of the cladding layer obtained by Example 10 and Example 12 of the present invention.

[0046] Fig.12 It is a microhardness curve diagram of the cladding layer obtained by Examples 12-15 of the present invention.

[0047] Fig.13 3 is a friction coefficient curve of the cladding layer prepared by Example 10 and Example 12 of the present invention.

[0048] Fig.14 1 is a graph showing the friction coefficient of the cladding layer obtained from Examples 12-15 of the present invention.

[0049] Fig.15 1 is a polarization curve diagram of the cladding layer obtained by Examples 12-15 of the present invention.

[0050] Fig.16 It is a macroscopic morphology of the cladding layer obtained by Examples 16-19 of the present invention.

[0051] Fig.17 It is the XRD spectrum of the cladding layer prepared by Examples 16-19 of the present invention.

[0052] Fig.18 It is a microhardness curve diagram of the cladding layer obtained by Examples 16-19 of the present invention.

[0053] Fig.19 Graph showing the coefficient of friction of the cladding layers obtained from Examples 16-19 of the present invention.

[0054] Fig. 20 It is a polarization curve diagram of the cladding layer obtained by Examples 16-19 of the present invention. DETAILED DESCRIPTION

[0055] The following is combined with the embodiments and the attached Figure 1-20 The present invention is described in further detail.

[0056] Example 1

[0057] This embodiment provides a laser cladding method for improving the wear resistance of a cladding layer on a surface of a stainless steel substrate, comprising the following steps:

[0058] 1) Selecting a 27SiMn steel substrate as a metal substrate, cleaning the surface of the 27SiMn steel substrate, wherein the 27SiMn steel substrate comprises the following components in weight percentage: 0.24-0.32% C, 1.10-1.40% Si, 1.10-1.40% Mn, 0.10-0.30% Cr, 0.10-0.30% Ni, 0.10-0.30% Cu, 0.05-0.15% Mo and the balance Fe;

[0059] 2) Select wire material as laser cladding material. The diameter of the wire material is 1.2 mm. The wire material includes 17-4PH wire material and 420 wire material. The mass ratio of 17-4PH wire material and 420 wire material is 2:1. Preheat the 17-4PH wire material and 420 wire material to 800-850°C to obtain laser cladding material.

[0060] 3) A high-speed wire laser cladding processing system was used, the laser wavelength was set to 1064 nm, the spot diameter was 4 mm, the 17-4PH wire stock and 420 wire stock discs in step 2) were mounted on the wire feeding wheel, and extended to the conductive nozzle, the feeding method was lateral wire feeding, and nitrogen with a purity of 99.99% was selected as the protective gas, the power was adjusted to 2800 W, the scanning speed was 25 mm / s, and the total wire feeding speed was 62 mm / s, wherein the wire feeding rate of the 17-4PH wire stock was 41.3 mm / s, and the wire feeding rate of the 420 wire stock was 20.7 mm / s, and a cladding layer was obtained on the surface of the 27SiMn steel substrate.

[0061] Example 2

[0062] The present embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. The difference from Embodiment 1 is that in the present embodiment, the mass ratio of 17-4PH wire stock and 420 wire stock is 1:1, the wire feeding rate of 17-4PH wire stock is 31 mm / s, the wire feeding rate of 420 wire stock is 31 mm / s, and the remaining steps are the same as those in Embodiment 1.

[0063] Example 3

[0064] The present embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. The difference from Embodiment 1 is that in the present embodiment, the mass ratio of 17-4PH wire stock and 420 wire stock is 1:2, the wire feeding rate of 17-4PH wire stock is 20.7 mm / s, the wire feeding rate of 420 wire stock is 41.3 mm / s, and the remaining steps are the same as those in Embodiment 1.

[0065] Example 4

[0066] The present embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. The difference from Embodiment 1 is that in the present embodiment, the mass ratio of 17-4PH wire stock and 420 wire stock is 1:3, the wire feeding rate of 17-4PH wire stock is 15.5 mm / s, the wire feeding rate of 420 wire stock is 46.5 mm / s, and the remaining steps are the same as those in Embodiment 1.

[0067] Example 5

[0068] This embodiment provides a laser cladding method for improving the wear resistance of a cladding layer on a surface of a stainless steel substrate, comprising the following steps:

[0069] 1) Selecting a 27SiMn steel substrate as a metal substrate, cleaning the surface of the 27SiMn steel substrate, wherein the 27SiMn steel substrate comprises the following components in weight percentage: 0.24-0.32% C, 1.10-1.40% Si, 1.10-1.40% Mn, 0.10-0.30% Cr, 0.10-0.30% Ni, 0.10-0.30% Cu, 0.05-0.15% Mo and the balance Fe;

[0070] 2) Select powder materials as laser cladding materials, the powder materials include 17-4PH powder materials, place the 17-4PH powder materials in a planetary ball mill for ball milling, set the speed to 150 rpm, run for 2 hours, the particle size of the 17-4PH powder materials is 45-100 μm, and the laser cladding materials are obtained;

[0071] 3) A fiber laser cladding processing system was used, the laser wavelength was set to 900-1080 mm, the spot diameter was 3 mm, the powder reserve material was spread on the metal substrate with a thickness of 1 mm by pre-setting the powder, nitrogen was selected as the protective gas, the power was adjusted to 1200 W, the scanning speed was 10 mm / s, and the overlap rate was 40%, and a cladding layer was obtained on the surface of the 27SiMn steel substrate.

[0072] Example 6

[0073] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. The difference from Embodiment 5 is that the power of the fiber laser cladding processing system in this embodiment is 1400 W, and the remaining steps are the same as those in Embodiment 5.

[0074] Example 7

[0075] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. The difference from Example 6 is that the power of the fiber laser cladding processing system in this embodiment is 1600 W, and the remaining steps are the same as those in Example 6.

[0076] Example 8

[0077] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. The difference from Example 6 is that the power of the fiber laser cladding processing system in this embodiment is 1800 W, and the remaining steps are the same as those in Example 6.

[0078] Example 9

[0079] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. The difference from Example 6 is that the power of the fiber laser cladding processing system in this embodiment is 2000W, and the remaining steps are the same as those in Example 6.

[0080] Example 10

[0081] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. The difference from Embodiment 9 is that the scanning speed in this embodiment is 8 mm / s, and the remaining steps are the same as those in Embodiment 9.

[0082] Embodiment 11

[0083] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. The difference from Embodiment 9 is that the scanning speed in this embodiment is 6 mm / s, and the remaining steps are the same as those in Embodiment 9.

[0084] Example 12

[0085] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. Unlike Example 10, the powder material in this embodiment also includes TiC powder and element B. The mass fraction of the TiC powder in the powder material is 0.8%, and the mass fraction of the B element is 0%. The remaining steps are the same as those in Example 10.

[0086] Embodiment 13

[0087] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. Unlike Example 10, the powder material in this embodiment also includes TiC powder and B element. The mass fraction of TiC powder in the powder material is 0.8%, and the mass fraction of B element is 0.4%. The remaining steps are the same as those in Example 10.

[0088] Embodiment 14

[0089] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. Unlike Example 10, the powder material in this embodiment also includes TiC powder and B element. The mass fraction of TiC powder in the powder material is 0.8%, and the mass fraction of B element is 0.8%. The remaining steps are the same as those in Example 10.

[0090] Embodiment 15

[0091] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. Unlike Example 10, the powder material in this embodiment also includes TiC powder and element B. The mass fraction of the TiC powder in the powder material is 0.8%, and the mass fraction of the B element is 1.4%. The remaining steps are the same as those in Example 10.

[0092] Example 16

[0093] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. Unlike Example 10, the powder material in this embodiment also includes C element and Mo element. The mass fraction of the C element in the powder material is 0.15%, and the mass fraction of the Mo element is 1%. The remaining steps are the same as those in Example 15.

[0094] Embodiment 17

[0095] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. Unlike Example 10, the powder material in this embodiment also includes element C, and the mass fraction of element C in the powder material is 0.15%. The remaining steps are the same as those in Example 15.

[0096] Embodiment 18

[0097] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. Unlike Example 10, the powder material in this embodiment also includes C element and Mo element. The mass fraction of the C element in the powder material is 0.1%, and the mass fraction of the Mo element is 1%. The remaining steps are the same as those in Example 15.

[0098] Embodiment 19

[0099] This embodiment provides a laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate. Unlike Example 10, the powder material in this embodiment also includes element C, and the mass fraction of element C in the powder material is 0.1%. The remaining steps are the same as Example 15.

[0100] Performance testing

[0101] The metal modified laser cladding surface cladding layer was prepared according to the preparation methods of Examples 1-24 respectively.

[0102] Reference Figure 1 , Figure 1 The cross-sectional macroscopic morphology of the cladding layer prepared in Example 1-4, (a) 17-4PH:420-2:1; (b) 17-4PH:420=1:1; (c) 17-4PH:420-1:2; (d)

[0103] 17-4PH:420=1:3. No defects such as pores and cracks were found in the cross-sectional images of the cladding layers obtained in Examples 1-4, indicating that the fusion between the multiple passes was good and the laser fuse process was stable.

[0104] Reference Figure 2 , Figure 2 The XRD patterns of the cladding layers prepared in Examples 1-4 are shown in Table 1. The cladding layers were analyzed by XRD. The phase compositions of the cladding layers prepared in Examples 1-4 are basically the same, which are α-Fe, a small amount of γ-Fe and M 23 C 6 、M 2 C.M. 7 C 3 Carbide; α-Fe is mainly martensite, and M in carbide represents Fe, Cr, Nb, etc.; with the increase in the proportion of 420 wire spare material, it can be seen in the spectrum that the diffraction peak intensity of carbides at about 42°, 44°, 51°, 64° and 81° increases, indicating that the carbide content increases.

[0105] Reference Figure 3 , Figure 3 The microhardness diagram of the cladding layers prepared in Examples 1-4 is shown. By testing the microhardness of the cladding layers prepared in Examples 1-4 in a direction perpendicular to the cladding layers, it can be seen that the hardness of the cladding layers prepared in Examples 1-4 is much higher than the hardness of the 27SiMn steel substrate (244.7HV 0.3 ), both at 500HV 0.3 As shown above, with the increase of the proportion of 420 wire reserve, the hardness of the cladding layer shows an upward trend. The hardness of the cladding layer prepared by Example 4 is the highest, which is 626.6HV. 0.3 The main reason is that the increase in C content causes an increase in the amount of high-hardness carbide precipitation. The hardness value error range of the cladding layer area obtained in Examples 1-4 is small, indicating that the cladding area has a uniform structure; the large hardness error when entering the heat-affected zone is because the combination of the cladding layer and the substrate is an arc shape when observed from the cross section, and some hardness points at the same depth belong to the cladding layer and some belong to the heat-affected zone.

[0106] Reference Figure 4 , Figure 4 The friction coefficient diagram of the cladding layer prepared by Examples 1-4 is shown in Figure 1. In the friction and wear performance test, Si 3 N 4The ceramic ball and the cladding layer obtained in Examples 1 to 4 were subjected to a circumferential friction test, and the friction coefficient was obtained simultaneously. The test was conducted at room temperature with dry friction without lubrication. During the dry friction process, the abrasive particles generated by wear are prone to secondary wear of the material, or are embedded in and attached to the surface of the material during repeated pressurized friction, resulting in a complex wear mechanism.

[0107] Reference Figure 4 , with the increase of the proportion of 420 wire spare material, the friction coefficient of the cladding layer shows a trend of first decreasing and then increasing. After 5 minutes of friction and wear test, the average friction coefficient of the cladding layer tends to be stable, and the average friction coefficients are 0.772, 0.649, 0.553 and 0.604 respectively. Under the shear stress of friction, adhesion points attached to the surface of the material are generated, and sliding occurs in the subsequent friction process, causing fluctuations in the friction coefficient. The cladding layers prepared by Examples 3 and 4 have a lower friction coefficient and a small fluctuation in the friction coefficient value.

[0108] Reference Figure 5 , Figure 5 The wear morphology of the cladding layer obtained by Examples 1-4. For the cladding layer obtained by Examples 1-2, due to its low surface hardness, the wear surface is severely deformed and scratches appear. During the sliding process, the test surface undergoes plastic deformation, the surface material separates and produces wear debris. As the sliding distance increases, these separated materials and wear debris lead to adhesive wear and abrasive wear. The surface of the cladding layer obtained by Example 3 undergoes slight adhesive wear and abrasive wear, and no plastic deformation occurs, indicating that it has good wear resistance. The cladding layer obtained by Example 4 produces deeper scratches due to the friction of hard particles, and oxidized particles can be observed, indicating that the wear mechanism is mainly abrasive wear, and oxidative wear occurs at the same time.

[0109] Reference Figure 6 , Figure 6 It is a polarization curve diagram of the cladding layer obtained by Examples 1-4. The corrosion performance of the samples is tested in a three-electrode electrochemical workstation. By applying different electrode potentials to the sample materials and measuring their current density, the polarization curve is obtained, and the self-corrosion potential and self-corrosion current density are obtained according to the Tafel extrapolation method, thereby studying the corrosion behavior of the samples.

[0110] Reference Figure 6 The self-corrosion potential of the cladding layer obtained in Example 1 is -0.547 V, and the self-corrosion current density is 4.688 e -6 A / cm 2 When the ratio of 420 wire material is increased, the self-corrosion potential of the cladding layer obtained by Example 2 is reduced to -0.594V, and the self-corrosion current density is 3.771e- 6 A / cm 2, which means that the corrosion resistance is reduced, but the corrosion rate is relatively reduced; the self-corrosion potential of the cladding layer obtained by Example 3 is increased to -0.542V, and its self-corrosion current density is reduced to 3.503e -6 A / cm 2 , indicating that it has good corrosion resistance and low corrosion rate; the self-corrosion potential of the cladding layer prepared by Example 4 is significantly lower than that of the cladding layer prepared by Example 3, which is -0.768V, and the self-corrosion current density is higher, which is 3.922e -6 A / cm 2 , indicating that its corrosion resistance is relatively poor. It can be seen from the comprehensive that the corrosion resistance of the cladding layers prepared by Examples 1-4 is better than that of the 27SiMn steel substrate. Compared with the 27SiMn steel substrate (-0.878V), the self-corrosion potential of the cladding layers is increased by 37.70%, 32.35%, 38.27% and 12.53%, respectively. Among them, the cladding layers prepared by Examples 2-3 have better corrosion resistance, and the corrosion rates are all in the first level.

[0111] Reference Figure 7 , Figure 7 The hardness diagram of the cladding layer obtained by Examples 5-11 shows that the microhardness of the cladding layer is positively correlated with the laser power used for cladding. When the laser power is low, the irradiation energy is not conducive to the metallurgical bonding of the material, and the microhardness of the alloy layer is low. With the increase of power, the metallurgical bonding strength between the cladding material and the base metal increases, and the microhardness shows an upward trend. When the laser power continues to increase, at a higher energy, the influence of the base on the composition of the alloy powder increases, and it will cause the burning of the alloy composition, and the trend of microhardness change weakens. With the increase of scanning speed, the hardness of the cladding layer gradually decreases, but the amplitude of change is small. This is because the increase in scanning speed leads to a decrease in irradiation energy per unit time and a decrease in metallurgical bonding strength, but at the same time, the time the laser beam acts on the molten pool is reduced, the cooling rate of the molten pool increases, and there is a certain degree of fine grain strengthening effect, so the microhardness does not change much.

[0112] Reference Figure 8 , Figure 8 The cross-sectional macroscopic morphology of the cladding layer obtained by Examples 12-15 is shown. After laser cladding, the cladding layer was subjected to flaw detection and found that crack defects appeared in the cladding layer obtained by Example 13, mostly existing at the overlap of the tracks and distributed in parallel. The laser cladding process is accompanied by high thermal stress. Due to the uneven distribution of hard borides in the cladding layer with a mass fraction of 0.4% B element, stress is easily concentrated to form cracks. The crack direction of the cladding layer obtained by Example 13 is parallel to the thickness direction of the cladding layer and almost penetrates the cladding layer. The crack extension direction is affected by the growth direction of the laser cladding tissue and shows longitudinal growth. The cladding layers obtained by Examples 12, 14 and 15 are all well formed.

[0113] Reference Fig. 9 , Fig. 9 The XRD patterns of the cladding layers obtained in Examples 12-15 show that the boron-free cladding layers with TiC added have martensite (α) phase and M 23 C 6 Type carbide phase, its M 23 C 6 The peak of M is higher than the corresponding peak in 17-4PH, and TiC is not detected. During the cladding process, as the temperature rises to the melting point of TiC, the ceramic phase can be decomposed into Ti and C in the metal solution. From a thermodynamic point of view, within the cladding temperature range, M 23 C 6 The Gibbs free energy is negative and lower than that of TiC, and the reaction can proceed spontaneously. It reacts with elements such as Fe to form new compounds or solid solutions. After adding the B element, the matrix phase does not change, mainly martensite and a small amount of austenite. Through the eutectic reaction, a phase mainly composed of M 2 (C, B) and M 7 (C, B) 3 The eutectic phase is composed of type carboride (M represents elements such as Fe, Cr, and Mn).

[0114] Reference Fig.10 , Fig.10 The microstructure of the cladding layer obtained in Examples 12-15 is shown in Figure 1. After grinding and polishing, the cladding layer obtained in Examples 12-15 was treated with 5g FeCl 3 +2mlHCl+99mlC 2 H 5 The etching reagent with OH ratio etches the cladding layer prepared by Examples 12-15 for about 14 seconds. During the laser action, the large amount of energy generated causes the temperature to quickly reach the melting point of the cladding material, and the alloy powder is quickly melted. During the cooling process of the molten pool, it first reaches the liquidus temperature and solidifies into high-temperature ferrite. As the temperature decreases, it undergoes a peritectic transformation to form austenite. The rapid cooling characteristics of laser cladding cause the austenite to eventually transform into martensite. The microstructure of each cladding layer is mainly martensite, containing a small amount of ferrite and residual austenite. Fig.10 It can be seen that the point-like precipitates are evenly distributed in the cladding layer structure. The cladding layer structure is mainly composed of thin and long lath martensite, containing a small amount of ferrite and residual austenite, and the original austenite grain boundary formation can be observed, among which the austenite grains of the cladding layer prepared by Example 14 are the smallest.

[0115] Reference Fig.11 , Fig.11The microhardness curve of the cladding layer obtained in Example 10 and Example 12 shows that the cladding layer can be roughly divided into three regions: cladding zone, heat affected zone and substrate. The addition of TiC powder significantly improves the microhardness of the stainless steel cladding layer, and the average microhardness increases from 422.1HV to 54.8HV. 0.3 Increased to 498.6HV 0.3 The improvement is 18.14%. The microhardness of the 17-4PH cladding layer without TiC powder fluctuates greatly. The reason is that the indentation size in the microhardness test is very small, and the hardness of martensite and ferrite in the microstructure is different. Therefore, the hardness fluctuations at the same depth are caused by the uneven structure.

[0116] Reference Fig.12 , Fig.12 The microhardness curves of the cladding layers obtained in Examples 12-15 are as follows. The average maximum hardness of the cladding layers is 498.6 HV 0.3 、525.0HV 0.3 、566.3HV 0.3 and 572.0HV 0.3 The addition of element B forms Fe 2 B (1430~1480HV) and (Cr,Fe) 7 (C,B) 3 The hardness of the cladding layer is significantly improved, and the hardness gradually increases with the increase of the B element content. The hardness of the cladding layer obtained by Example 15 reaches the highest, i.e., 572.0 HV 0.3 Compared with the cladding layer obtained in Example 12, the hardness is increased by 14.7%.

[0117] Reference Fig.13 , Fig.13 This is a friction coefficient curve diagram of the cladding layers prepared by Example 10 and Example 12. It can be seen that both curves have a gentle trend, and the cladding layer with added TiC powder has a lower friction coefficient.

[0118] Reference Fig.14 , Fig.14 The friction coefficient curves of the cladding layers obtained from Examples 12 to 15 show that with the increase of the B element content, the friction coefficient shows a trend of first decreasing and then increasing. The friction coefficients of the cladding layers obtained from Examples 12 to 15 are 0.715, 0.683, 0.532 and 0.582, respectively, indicating that adding an appropriate amount of B element can significantly reduce the friction coefficient of the alloy. The cladding layer obtained from Example 14 performs best. At this time, the friction coefficient curve is stable and the friction coefficient is low. The average friction coefficient in the stable stage of 5 to 30 minutes is 0.532, which is significantly lower than that of the boron-free cladding layer.

[0119] Reference Fig.15 , Fig.15 The polarization curves of the cladding layers prepared in Examples 12-15 are shown in FIG. 14. The cladding layer prepared in Example 13 is reduced to -0.484 V, and the self-corrosion current density is increased from 1.48e -6 A / cm 2 Increased to 2.517e -6 A / cm 2 , indicating that the corrosion resistance has decreased; the self-corrosion potential of the cladding layer obtained by Example 14 increased to -0.437V, and its self-corrosion current density was low, which was 2.085e -6 A / cm 2 , indicating that it has good corrosion resistance and low corrosion rate; the potential of the cladding layer prepared in Example 15 is -0.474V, and the self-corrosion current density is relatively high, which is 2.827e -6 A / cm 2 , indicating that its corrosion resistance is poor. Compared with the 27SiMn substrate, the corrosion resistance of the cladding layer is greatly improved. Judging from the comprehensive self-corrosion potential and self-corrosion potential density, the corrosion resistance of the cladding layer prepared by Example 12 and Example 14 is better.

[0120] Reference Fig.16 , Fig.16 The macroscopic morphology of the cladding layer obtained by Examples 16-19 is shown. After laser cladding, the cladding layer is subjected to flaw detection, and it can be seen that no crack defects are found on the surface of the cladding layer, indicating that the fusion between multiple passes is good.

[0121] Reference Fig.17 , Fig.17 The XRD patterns of the cladding layers obtained in Examples 16-19 are as follows. The γ-Fe diffraction peaks in the cladding layer samples obtained in Examples 17 and 19 are relatively strong, the content of retained austenite is relatively high, and part of C combines with Fe to form Fe 3 After the addition of Mo, the diffraction peaks at 29°, 41°, and 50° weakened, and the diffraction peaks at 44°, 75°, and 82° increased, indicating that Mo in carbides 7 C 3 、M 2 The content of C decreases, M 23 C 6 After adding Mo, the alloy is prone to form Mo 2 C, resulting in a decrease in the C concentration in the matrix phase. The Mo element has the effect of inhibiting the growth of austenite in the iron-based alloy, which can refine the structure of the cladding layer.

[0122] Reference Fig.18 , Fig.18The microhardness curves of the cladding layers obtained from Examples 16-19 show that the hardness curves tend to be consistent, with the microhardness values ​​gradually decreasing from the top of the cladding to the substrate, and the hardness sharply decreasing in the bonding area until the hardness of the substrate gradually stabilizes. Due to the differences in the molten heights of the cladding layers, the positions of the sudden hardness drops are different. From the microhardness of the cladding layers obtained from Examples 17 and 19, it can be seen that the microhardness of the cladding layers is significantly improved after the C content increases; from the microhardness of the cladding layers obtained from Examples 16 and 19, it can be seen that the addition of Mo slightly decreases the microhardness.

[0123] Reference Fig.19 , Fig.19 The friction coefficient diagram of the cladding layer prepared by Examples 16-19 is lower than that of the cladding layer prepared by Examples 16-19. The higher the C content, the lower the friction coefficient of the cladding layer. When the C content is constant, adding Mo element can effectively reduce the friction coefficient of the cladding layer. After stabilization, the average friction coefficients of 17-4PH and the cladding layer prepared by Examples 16-19 are 0.753, 0.646, 0.598, 0.554 and 0.493 respectively.

[0124] Reference Fig. 20 , Fig. 20 The polarization curves of the cladding layers obtained from Examples 16-19 show that the self-corrosion potential of the 17-4PH cladding layer is -0.496 V, and the self-corrosion current density is relatively low, which is 1.216 e -6 A / cm 2 , indicating that the 17-4PH cladding layer has good corrosion resistance and low corrosion rate; with the increase of C content, the self-corrosion potential of the cladding layer gradually decreases, the self-corrosion current density increases, and the corrosion resistance of the cladding layer shows a downward trend. From the performance of the cladding layers prepared in Examples 16 and 17, it can be seen that adding Mo to the alloy can effectively increase its self-corrosion potential, reduce the self-corrosion current density, and have better corrosion resistance.

[0125] The above are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A laser cladding method for improving the wear resistance of a cladding layer on a stainless steel substrate, characterized in that: The steps include: S1. Select a metal substrate and clean the metal substrate; S2, selecting laser cladding materials, pre-treating the laser cladding materials, and obtaining laser cladding spare materials; S3, using a laser cladding process to clad the laser cladding spare material in step S2 on the surface of the metal substrate prepared in step S1; The metal substrate in step S1 is a 27SiMn steel substrate; The laser cladding material in step S2 includes any one of wire material or powder material.

2. The laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate according to claim 1, characterized in that: The 27SiMn steel substrate comprises the following components in weight percentage: 0.24-0.32% C, 1.10-1.40% Si, 1.10-1.40% Mn, 0.10-0.30% Cr, 0.10-0.30% Ni, 0.10-0.30% Cu, 0.05-0.15% Mo and the balance Fe.

3. The laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate according to claim 1, characterized in that: The wire material spares in step S2 include 17-4PH wire material spares and 420 wire material spares; The diameter of the spare wire material in step S2 is 1.2 mm.

4. The laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate according to claim 3, characterized in that: The mass ratio of the 17-4PH wire material reserve and the 420 wire material reserve in step S2 is (1-2): (1-3).

5. The laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate according to claim 3, characterized in that: When the laser cladding material in step S2 is selected as the spare wire material, the pretreatment of the laser cladding material in step S2 is to preheat the spare wire material to 800-850° C. in advance.

6. The laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate according to claim 5, characterized in that: When the laser cladding material in step S2 is selected as the spare wire material, the laser cladding process in step S3 is to set the laser wavelength to 1064nm, the spot diameter to 4mm, the spare wire material tray is installed on the wire feeding wheel of the laser cladding equipment, and extended to the conductive nozzle, the feeding method is lateral wire feeding, nitrogen with a purity of 99.99% is selected as the protective gas, the power is adjusted to 2800W, the scanning speed is 25mm / s, and the total wire feeding speed is 62mm / s.

7. The laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate according to claim 1, characterized in that: The powder material in step S2 includes 17-4PH powder material; The particle size of the 17-4PH powder stock is 45-100 μm.

8. The laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate according to claim 6, characterized in that: When the laser cladding material in step S2 is selected from powder materials, the powder materials in step S2 are placed in a planetary ball mill for ball milling, the rotation speed is set to 150 rpm, and the mill is operated for 2 hours.

9. The laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate according to claim 6, characterized in that: When the laser cladding material in step S2 is selected as powder material, the laser cladding process in step S3 is to set the laser wavelength to 900-1080nm, the spot diameter to 3mm, and the powder material is spread on the metal substrate with a thickness of 1mm by pre-setting the powder, nitrogen is selected as the protective gas, the power is adjusted to 1200-2000W, the scanning speed is 6-10mm / s, and the overlap rate is 40%.

10. The laser cladding method for improving the wear resistance of the cladding layer on the surface of a stainless steel substrate according to claim 5, characterized in that: The powder material in step S2 further includes one or more of TiC powder, B element, Mo element and C element; The mass fraction of TiC powder in the powder material in step S2 is 0-1%, and the particle size of TiC is 45-109 μm; The mass fraction of element B in the powder material in step S2 is 0-1.4%; The mass fraction of Mo element in the powder material in step S2 is 0-0.15%; The mass fraction of the C element in the powder material in step S2 is 0-1%.